The Boundaries of the Southern Aukštaitian Dialect: the Change in the Pronunciation of Diphthongs in the Subdialect of Šalčininkai Area - Tuomienė, Nijolė (Acta humanitarica academiae Saulensis, 2023)
In this article, from a synchronic point of view, the particularities of the change in the pronunciation of the diphthongs ie and uo are analyzed in the dialect of Šalčininkai area, which is located on the border of the Southern Aukštaitians dialect. The audio recordings of the second half of the 20th century have been analysed. They are consistent Lithuanian texts recorded by the last representatives of this dialect. The research aims to reveal the possible reasons for the change in the pronunciation of the diphthongs ie and uo, considering the fact that the Lithuanian language was and still is not the only language in this region.The research considers the sociolinguistic situation in the region, which influenced the development and change of language functioning in the analysed area. The surroundings of the entire Šalčininkai district were enslaved at different rates. In the surroundings of Butrimonys, Gudeliai, Eišiškės, Kalesninkai, and Turgeliai, the Lithuanian language remained less compact and began to disintegrate faster, so the results of the diversification of ie and uo dialects are not the same. Instead of diphthongs, the frequent pronunciation of long vowels is fixed here – accented and unaccented ie, uo is pronounced as i, u. In Vėžionis, Didžiosios Sėlos the situation is different, so here both vowels are pronounced in these diphthongs.The research revealed that the pronunciation of diphthongs ie, uo in Šalčininkai dialect varies in various positions: from ie, uo or ie, uo to completely long i, u. The tendency of representatives of the Lithuanian dialect to unify these diphthongs is observed in Lithuanian dialects that are in contact with East Slavic languages. In the case under consideration – with Polish and local Belarusian dialects. Due to the population’s longterm bilingualism and the internal development of the language, the long vowels in the Lithuanian language have become shorter, and their quality has changed. The dephonologisation of accusatives recorded in the dialect also accelerated the process of monophtogization of diphthongs. In the studied dialect of Šalčininkai, the unison of diphthongs becomes universal. Most native speakers almost systematically monophthongize stressed and unstressed ie, uo. In rare cases, both vowels in the diphthongs were pronounced only by the oldest representatives of the language.
Keywords: Southern Aukštaitian dialect; border subdialect of Šalčininkai; language contacts; change of quality and quantity of vowels; monophthongization of diphthongs